2014
DOI: 10.4161/biom.28535
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a SiO2coating on the corrosion parameters cpTi and Ti-6Al-7Nb alloy

Abstract: The aim of this paper was to evaluate the usefulness of the sol-gel method application, to modificate the surface of the Ti6Al7Nb alloy and the cpTi titanium (Grade 4) with SiO2 oxide, applied on the vascular implants to improve their hemocompatibility. Mechanical treatment was followed by film deposition on surface of the titanium samples. An appropriate selection of the process parameters was verified in the studies of corrosion, using potentiodynamic and impedance method. A test was conducted in the solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…On the basis of the obtained results, it was found that regardless of the applied surface treatment the values of critical force causing delamination of the layers was similar and was equal to Lc 3 = 3.80 N (for the polished sample with the Al 2 O 3 layer) and Lc 3 = 3.81 N (for the polished and passivated sample with the Al 2 O 3 layer) respectively - Fig. 3 [12][13][14]. Regardless of the substrate material during the test the acoustic emission signal was not recorded which indicates that the energy of the bond between the coating and the substrate was too low.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of the obtained results, it was found that regardless of the applied surface treatment the values of critical force causing delamination of the layers was similar and was equal to Lc 3 = 3.80 N (for the polished sample with the Al 2 O 3 layer) and Lc 3 = 3.81 N (for the polished and passivated sample with the Al 2 O 3 layer) respectively - Fig. 3 [12][13][14]. Regardless of the substrate material during the test the acoustic emission signal was not recorded which indicates that the energy of the bond between the coating and the substrate was too low.…”
Section: Resultsmentioning
confidence: 99%
“…Pitting corrosion test was performed for the samples of the particular variants of surface treatment by potentiodynamic method (recording of anodic polarization curves). On this basis characteristic parameters were set: corrosion potential E kor [ direction of polarization was changed (the return curve was recorded) [12][13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impedance spectra were analysed with the use of equivalent circuits, and their resultant impedances described ( Figure 4 and Table 2). The best conformity between the model spectra and the experimental spectra obtained from the artificial plasma was achieved in the following circuits: 5,6,11 • circuit indicating the existence of a double layer, where R s is the resistance of the artificial plasma, CPE p is a constant phase element modelling the capacity of the surface zone of the material, with a highly developed surface, R p -an element modelling the solution resistance in this zone, R ct and CPE dlresistance and capacity of the oxide layer (Figure 4a), • circuit including also CPE pore -an element representing the capacity of a double (porous) layer and an R pore resistor representing the electrolytic resistance in the pores (Figure 4b). …”
Section: Resultsmentioning
confidence: 99%
“…The development and verification of conditions for coating cpTi with layers of TiO 2 and SiO 2 characterized by high hemocompatibility was the topic of previous papers published by the authors. [5][6][7] The safety of a medical device involving contact with blood is also related to the necessity of observing the appropriate procedures, preventing the transfer of pathogenic microorganisms into the human body. Such procedures are aimed at the removal and efficient elimination of microorganisms and the obtaining of sterile medical devices complying with certain specified quality requirements.…”
Section: Introductionmentioning
confidence: 99%